Hydrocracking Aspal Buton Dengan Katalisator Nikel-Paladium, Ni-Pd Dalam Pengemban Zeolit. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Preparation of bimetal Ni-Pd/zeolite catalysts and the effect of Ni/Pd concentraion towards their characters in hydrocracking of asphaltene from Butonion asphalt have been studied. The aspaltene was a pentane insoluble-benzene soluble (PI-BS) fraction of Butonion asphalt. The catalyst preparations were carried out by impregnating a small amount of nickel and Palladium onto zeolite. The catalysts were calcined, oxidized and reduced by nitrogen, oxygen and hydrogen gas at 400 Â°C, respectively. The characterizations of catalysts by means determination of Ni and Pd contents